2015
DOI: 10.1111/1748-8583.12075
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of works councils: the role of trust, justice and industrial relations climate

Abstract: This paper investigates trust and organizational justice as antecedents of Works Council (WC) effectiveness perceptions, and the moderating role of industrial relations climate on this relationship. A two-year longitudinal study of Works Council participants in two UK organizations (a Housing Association and a Professional Services firm) was undertaken.Results show positive significant relationships between both trust and organizational justice and WC outcomes of WC performance, WC usefulness, and outcome sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 77 publications
0
17
0
Order By: Relevance
“…As the Commission noted in 1998, ‘Information and Consultation are factors for productivity as they contribute to the creation of a highly skilled and committed workforce’ (CEC, 1998: 2). As such there is a need to redefine ‘effectiveness’ beyond employee interests and the democratisation of the workplace (see also Kougiannou et al, 2015) and consider the implications of mandated consultation for the managerial and practitioner constituency. Certainly, within the UK, the legitimising rhetoric surrounding the transposition of the ICE Regulations in 2004 was couched in terms of the latter ‘business case’ (Gollan and Wilkinson, 2007: 1148) narrative.…”
Section: Ice: Stakeholder Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…As the Commission noted in 1998, ‘Information and Consultation are factors for productivity as they contribute to the creation of a highly skilled and committed workforce’ (CEC, 1998: 2). As such there is a need to redefine ‘effectiveness’ beyond employee interests and the democratisation of the workplace (see also Kougiannou et al, 2015) and consider the implications of mandated consultation for the managerial and practitioner constituency. Certainly, within the UK, the legitimising rhetoric surrounding the transposition of the ICE Regulations in 2004 was couched in terms of the latter ‘business case’ (Gollan and Wilkinson, 2007: 1148) narrative.…”
Section: Ice: Stakeholder Outcomesmentioning
confidence: 99%
“…However, such a design is likely to lack the sensitivity to capture subtle changes in process, attitudinal improvements (Johnstone et al, 2009) and advances (or otherwise) in the antecedents of effective consultation, e.g. trust (Kougiannou et al, 2015). Such dynamics typically occur through minor and incremental adjustments.…”
Section: Opportunities For Theory Buildingmentioning
confidence: 99%
“…Information and consultation (I&C) bodies are one of the most common forms of representative participation in non-union firms (Gollan and Xu 2007;Van Wanrooy et al, 2013). A key debate concerns trust relations between principal actors within I&C bodies (Dietz and Fortin, 2007;Kougiannou, Redman and Dietz, 2015). Several attempts have been made to assess the effectiveness of I&C processes (Adam, Purcell and Hall, 2014;Cullinane et al, 2014;Holland et al, 2009), however, research on the critical issues of trust and justice between the parties is limited despite their Acknowledgments: The work presented in this paper owes a debt to Tom Redman and Graham Dietz, for their guidance and support during the early stages of preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Most of all, we miss their friendship. centrality to the process (Kougiannou, Redman and Dietz, 2015). Broad (1994) found that a mismatch in participant expectations led to a fragile voice arrangement and Kessler and Purcell (1996) expressed concern about the limited attention paid to the factors that make joint consultative processes effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation